A book for black-eyed Susan - Young, Judy.; Ettlinger, Doris (Ann Arbor, MI : Sleeping Bear Press, 2011)
While traveling along the Oregon Trail, ten-year-old Cora and her newborn baby sister suffer the loss of their mother and are separated, but Cora stitches a book to tell the dark-eyed baby of their journey and family.
Kirkus Review, January 2011.
3.7
3-6
580L
Keywords: Books and reading -- Juvenile fiction; Sisters -- Juvenile fiction; Sewing -- Juvenile fiction; Overland journeys to the Pacific -- Juvenile fiction; Frontier and pioneer life -- Oregon -- Juvenile fiction; Books and reading -- Fiction; Sisters -- Fiction; Sewing -- Fiction; Overland journeys to the Pacific -- Fiction; Frontier and pioneer life -- Oregon -- Fiction; Historical fiction; Oregon Territory -- History -- Juvenile fiction; Oregon Territory -- History -- Fiction; Historical fiction